Influence of Innovation Orientation on Performance of Non-Life Insurance in Kenya (International Journal of Scientific Research and Management (IJSRM), 2024)
The insurance industry plays crucial role in the social and economic development of every economy. However, the non-life insurance sub-sector in Kenya has had performance downturn in the past ten years. This study sought to examine the effect of innovation orientation on the performance of non-life insurance in Kenya. The study was anchored on the Schumpeter’s theory. The target population of the study was 35 non-life insurance companies licensed by the insurance regulatory authority and members of the association of Kenya insurers. The study adopted survey research design and used questionnaires to collect primary data. A pilot study was done to test the reliability and validity of the research instrument. The study used Cronbach’s alpha (α) coefficient to test reliability, while construct and content validity were used to check the validity of the research instrument. The data was analyzed using quantitative and qualitative analysis statistics with the help of SSPS version 24. The study used correlation analysis, regression analysis and analysis of variance (ANOVA) to establish the relationship between the variables, strength and direction of the variables and to test hypotheses. The results were presented in tables and models. The study revealed that innovation orientation significantly influenced the performance of non-life insurance companies in Kenya. This meant that non-life insurance companies that prioritize innovation in their products, services, and processes are likely to achieve better performance outcomes. Given the significant impact of innovation orientation on performance, non-life companies should allocate more resources on research to increase gross written premium, insurance penetration and improve underwriting profits. The study recommends future research in other financial services sectors to establish the role of innovation orientation on performance of those sectors. The study focused on non-life insurance in Kenya which limits its application to a fast growing sub-sector of micro-insurance and recommends that a study be conducted on micro-insurance. The findings of such a study may be useful in aiding review of insurance regulations and policy